Massive Calcium Pyrophosphate Dihydrate Crystal Deposition Disease: A Cause of Pain of the Temporomandibular Joint - Marsot-Dupuch, Kathlyn (AJNR Am J Neuroradiol, 2004)
Summary: Calcium pyrophosphate dihydrate deposition (CPDD) disease is a disorder that occasionally affects the temporomandibular joint (TMJ) and temporal bone, causing pain (66.6% of cases), swelling (50%), trismus (36.8%), and hearing loss (22.2%). Diagnosis of CPDD is challenging because clinical symptoms and imaging features are not characteristic and may mimic a chondrosarcoma. When the diagnosis of CPDD of the TMJ is under consideration, conventional radiographs of the wrist or the knee may contribute to the final diagnosis. Imaging features of CPDD are discussed with a review of the literature.